Scrub typhus infection in a kidney transplant recipient: a case report - Dongyeon Lee; Joohee Jeon; Jae Sung Ahn; Chung Hee Baek (Kosin Medical Journal, 2023)
Scrub typhus is a febrile disease that is endemic to Asia and the Pacific region. Its clinical manifestations include fever, myalgia, lymphadenopathy, and a characteristic eschar. The main manifestations of this disease are difficult to differentiate from those of other febrile illnesses; thus, a careful clinical examination and a high index of suspicion are crucial for an early diagnosis. Our case involved a 55-year-old female renal transplant recipient who presented with fever and sore throat in November. Her clinical symptoms did not improve after oral amoxicillin/clavulanate administration for 7 days, after which proteinuria and acute kidney injury were identified. After hospitalization, an eschar was found and immunoglobulin M antibodies against Orientia tsutsugamushi were detected by indirect immunofluorescence. She received oral doxycycline for 7 days and showed improvement in renal function and proteinuria. This is the first case report of scrub typhus infection in a kidney transplant patient in Korea. It is meaningful to report that the renal abnormalities associated with scrub typhus improved in a renal transplant patient through treatment of the disease. This case highlights the importance of examining the social history and symptoms of patients suspected of having scrub typhus in endemic areas. Early diagnosis and treatment are crucial in kidney transplant patients to preserve graft function and prevent fatal complications.